Assessment of potential health impacts on surface water sources in Northern Nigeria - Umar, ZD; Bashir, A (International Journal of Environment, 2014)
Northern Nigeria represents the most populous region in Nigeria and adequate water supply and sanitation typically leaves a lot to be desired in the region in order to prevent water related diseases to the vulnerable communities of the region. This research work was carried out in Kano state with specific emphasis on Tomas dam which is one of the largest dams established for multipurpose use in Nigeria. The research was aimed at evaluating Physico-chemical and Bacteriological quality of Tomas Dam in Kano State. 240 water samples from 5 sampling stations within eight months were analyzed for bacteriological and physico-chemical quality. The physico-chemical parameters indicated Biochemical Oxygen Demand (BOD) and Water Current Speed results were not significantly different (P>0.05), while other physico-chemical parameters analyzed varied significantly (P